Dual‐Functional Ca‐Ion‐Doped Layered δ‐MnO2 Cathode for High‐Performance Aqueous Zinc‐Ion Batteries - Xie, Dongmei; Wang, Yan; Tian, Leiwu; Huang, Haiji; Sun, Jianyang; Kim, Dong‐Won; Zhao, Jiachang; Mao, Jianfeng (Advanced functional materials, 2025)
Aqueous zinc‐ion batteries (ZIBs) have gained significant attention owing to their high energy densities, low costs, and enhanced safety profiles. However, the development of suitable host materials (i.e., cathodes) with high capacity, structural stability, and rate performance remains challenging. Herein, a nanoflower‐like Ca0.10MnO2·0.61H2O (CaMnO) is successfully synthesized as a high‐performance cathode material for ZIBs using a simplified one‐step hydrothermal method. The unique nanoflower‐like 3D porous structure provides a continuous conductive path and abundant adsorption sites for Zn2+ ions and mitigates aggregation during long‐term cycling processes. In addition, doping Ca2+ ions into the interlayer of MnO2 has a dual functional effect: 1) it acts as a pillar to broaden the interlayer spacing and enhance the crystal structure stability, and 2) it induces the formation of oxygen vacancies to enhance the reaction kinetics and increase the reversible capacity. Therefore, the CaMnO cathode exhibits a high specific capacity of 289 mAh g−1, with excellent capacity retention (90%) over 750 cycles at a high current rate of 1.5 A g−1. This study provides a new perspective on the development of advanced cathode materials for ZIBs. This work proposes a δ‐MnO2 cathode with excellent Zn ion storage performance through morphology control (nanoflower‐like) and structural optimization (Ca2+‐doping). The bifunctional Ca2+ dopant improves the structural stability of the layered framework while inducing the formation of oxygen vacancies to improve reaction kinetics and enhance reversible capacity. Therefore, the optimized cathode exhibits excellent structural integrity and long‐term cycling stability.